The science of paddling, Part 2: Different strokes - Burke, S. (2009)
Perhaps the first paddling truism I ever learned is that tandem paddlers must always paddle in sync. Recently, I began wondering whether there really was any truth to that old saw. It turns out that there is, and the underlying reasons are both obvious, and unexpected.